Voltammetric studies of the interaction of copper(II) with melamine in Britton-Robinson buffer solution (Bangladesh Journal of Scientific Research, 2012)
Key words: Britton-Robinson buffer; cyclic voltammetry; copper(II); melamine; glassy carbon electrodeDOI: http://dx.doi.org/10.3329/bjsr.v24i2.10767Bangladesh J. Sci. Res. 24(2):107-116, 2011 (December)